Maintenance costs of road pavement and motor vehicles on the route Vilnius – Kaunas – Klaipeda - Miškinis, Dainius; Lingaitis, Vytautas (Transport, 2006)
The article describes the impact of axle loads of vehicles on the road pavement. Pavement deterioration intensity and the charge imposed on vehicles the axle load of which exceeds the set norm are analyzed on the road under investigation according to the results of weighing axle loads of vehicles as well as appropriate calculation methodologies. The work presents regressive equations according to which maintenance costs of vehicles can be predicted taking the condition of pavement into consideration. First Published Online: 27 Oct 2010